Acceleration of the partial element equivalent circuit method with uniform tessellation—part I: Identification of geometrical signatures. (4th December 2017) - Romano, Daniele; Lombardi, Luigi; Antonini, Giulio
Abstract: Electromagnetic numerical modeling has become crucial for the design deployment and operation of new electrical and electronic devices and systems especially for its capability to address electromagnetic compatibility and interference issues. In this regard, accurate and efficient numerical techniques are required for effective and fast virtual prototyping. This paper presents a novel technique to speedup the computation of partial elements describing the magnetic and electric field couplings in the framework of the partial element equivalent circuit method. When dealing with uniform tessellation of 3D geometries, including Manhattan‐type meshes and also nonorthogonal ones characterized by hexahedra with comparable sizes, a huge number of configurations are repeated under only translation and rotation transformations. Through an efficient identification of these geometrical signatures, the calculation of volume and surface integrals required to fill the partial element matrices, namely, partial inductances and coefficients of potential, can be significantly accelerated. To this aim, assuming a uniform tessellation of volumes and surfaces, a complete algorithm is presented to systematically identify all the signatures and manage them, thus allowing a significant speedup of the partial element matrices filling‐in process. Being based on a systematic identification of the different patterns, the proposed method does not introduce any approximation. Numerical examples are presented pointing out the correctness and efficiency of the proposed approach.